The Inflammatory Response in Human Keratinocytes Exposed to Cinnamaldehyde Is Regulated by Nrf2 - Romain Vallion; Kévin Hardonnière; Abderrahmane Bouredji; Marie-Hélène Damiens; Claudine Deloménie; Marc Pallardy; Pierre-Jacques Ferret; Saadia Kerdine-Römer (MDPI AG, 2022)
Keratinocytes (KC) play a crucial role in epidermal barrier function, notably through their metabolic activity and the detection of danger signals. Chemical sensitizers are known to activate the transcription factor nuclear factor (erythroid-derived 2)-like 2 (Nrf2), leading to cellular detoxification and suppressed proinflammatory cytokines such as IL-1β, a key cytokine in skin allergy. We investigated the role of Nrf2 in the control of the proinflammatory response in human KC following treatment with Cinnamaldehyde (CinA), a well-known skin sensitizer. We used the well-described human KC cell line KERTr exposed to CinA. Our results showed that 250 μM of CinA did not induce any Nrf2 accumulation but increased the expression of proinflammatory cytokines. In contrast, 100 μM of CinA induced a rapid accumulation of Nrf2, inhibited IL-1β transcription, and downregulated the zymosan-induced proinflammatory response. Moreover, Nrf2 knockdown KERTr cells (KERTr ko) showed an increase in proinflammatory cytokines. Since the inhibition of Nrf2 has been shown to alter cellular metabolism, we performed metabolomic and seahorse analyses. The results showed a decrease in mitochondrial metabolism following KERTr ko exposure to CinA 100 µM. In conclusion, the fate of Nrf2 controls proinflammatory cytokine production in KCs that could be linked to its capacity to preserve mitochondrial metabolism upon chemical sensitizer exposure.